Kewarisan Anak di Luar Perkawinan di Tengah Isu Gender - Wahidah, Wahidah (Muadalah, 2013)
Child before of marriage is basicly a term which definition is rather difficult to be correlated with the term natural child (ibn al mulaanah) as stipulated in fiqh. This difficulty is triggered by the " law " that define the term in a statement which create various interpretations from many people. In relation to inheritance issues, child before marriage or natural child inherits only from their mother and relatives, istead of their father. Such it is perceived as an inequality and injustice in the gender issues of the relationship between two different sexesâmale and female. Whereas both partiesâparents of the child before marriage, are the accursed who make possible the innocent child born into the world.